Antifungal Activity of Siderophore Isolated From Escherichia coli Against Aspergillus nidulans via Iron-Mediated Oxidative Stress - Khan, Azmi; Singh, Pratika; Kumar, Ravinsh; Das, Sujit; Singh, Rakesh Kumar; Mina, Usha; Agrawal, Ganesh Kumar; Rakwal, Randeep; Sarkar, Abhijit; Srivastava, Amrita (Frontiers in Microbiology, 2021)
Microorganisms produce various secondary metabolites for growth and survival. During iron stress they produce secondary metabolites termed siderophores. In the current investigation, antifungal activity of catecholate siderophore produced by Escherichia coli has been assessed against Aspergillus nidulans. Exogenous application of the bacterial siderophore to fungal cultures resulted in decreased colony size, increased filament length, and changes in hyphal branching pattern. Growth inhibition was accompanied with increased intracellular iron content. Scanning electron microscopy revealed dose-dependent alteration in fungal morphology. Fluorescent staining by propidium iodide revealed cell death in concert with growth inhibition with increasing siderophore concentration. Antioxidative enzyme activity was also compromised with significant increase in catalase activity and decrease in ascorbate peroxidase activity. Siderophore treated cultures showed increased accumulation of reactive oxygen species as observed by fluorescence microscopy and enhanced membrane damage in terms of malondialdehyde content. Antifungal property might thus be attributed to xenosiderophore mediated iron uptake leading to cell death. STRING analysis showed interaction of MirB (involved in transport of hydroxamate siderophore) and MirA (involved in transport of catecholate siderophore) confirming the possibility of uptake of iron-xenosiderophore complex through fungal transporters. MirA structure was modeled and validated with 95% residues occurring in the allowed region. In silico analysis revealed MirA-Enterobactin-Fe3+ complex formation. Thus, present study reveals a promising antifungal agent in the form of catecholate siderophore and supports involvement of MirA fungal receptors in xenosiderophore uptake.